MOTIVES OF CRIMINAL ACTS OF CORRUPTION IN INDONESIA - Seregig, I Ketut (Faculty of Law, Universitas Sebelas Maret, 2018)
The data presented in this study are legal facts that come from informants who are directly involved in the investigation of corruption crime at Lampung Provincial Health Office, conducted by the High Prosecutor Attorney Lampung as well as the Prosecutor and the decision of the Panel of Judges who tried the case of corruption of Ambulance procurement project, Mobile Hospital support unit, 4 WD Ambulance sourced from APBD Lampung Province in 2013 worth of IDR 7,600,000,000.00 (seven billion six hundred million rupiah). The result of research is that corruption crime in Indonesia is done by more than one perpetrator, which is divided in two variables that support each other that is between leader and subordinate. This variable is consistent with the conclusion of Lambsdorff's research which states